The Devil, Superstition, and the Fragmentation of Magic - Armstrong, Sean (Renaissance and Reformation / Renaissance et Réforme, 2014)
Using mostly English sources of the witch hunt era, this article demonstrates that the “fragmentation of Renaissance occultism” argued by John Henry and others involved redefining the term “superstition.” At the start of the witch hunt era, superstition was the antonym to religion; by the 1620s, when the witch hunt peaked, Francis Bacon was presenting his new philosophy as the antonym to superstition and its twin idolatry. This change in the signification of superstition was causally linked to the devil, who was both master and goal of all superstition and idolatry. Superstition was redefined and the devil was rethought as aspects of the same process, as critics of the witch hunt concluded that it was superstition to believe the devil could affect the natural order. The early stages of this redefinition drew on a concept from early classical natural philosophy that has been labelled “double determination” by G. E. R. Lloyd. Eventually the expanded concept of superstition became the counterfoil to the new philosophy.